Tensoresistive Properties of Thin Film Systems Based on Ag and Co - I.M. Pazukha; Z.M. Makukha; Yu.M. Shabelnyk; I.Yu. Protsenko (Журнал нано- та електронної фізики)
The results of research strain deformation properties of thin films Ag, Co and two-layers films Ag/Co in the range of deformation Δεl = 0-1 % were presented. The plastic deformation in Co layer caused a similar deformation in the entire film system, even if the strain range Ag layer is not reached the limits of the transition elastic/plastic deformation. The increasing of gauge factor value of two-layer systems in comparison with thin films Ag and Co appears as a result of electron interface scattering.